PENERAPAN METODE SIMPLE MULTI – ATTRIBUTE RATING TECHNIQUE (SMART) DALAM MENENTUKAN BAKAT ANAK USIA DINI - Erwin, Erwin Ginting; Nita, Nita Syahputri; Fithry, Fithry tahel; Dian, Dian Mayasari (Jurnal Multidisipliner Bharasumba, 2025)
This causes teachers to be able to develop potential interests and talents in children. The many potential interests and talents of children that must be taken into account make it difficult for teachers during the decision-making process to determine the direction of children's interests and talents and when filling out report cards, especially talent report cards. To solve this problem, we need a Decision Support System for the interests and talents of early childhood which can help the RA unit in determining the direction of children's interests and talents more effectively and efficiently. The data used in this research comes from early childhood talent report cards archived by teachers. The method used in this research is Simple Multi - Attribute Rating Technique (SMART), where this method is a multi-criteria decision making method which is based on the theory that each alternative consists of a number of criteria that have value and each criterion has a weight to describe how It is important to compare its value with other criteria. With this system, it is hoped that it can help teachers and parents to speed up data processing in determining early childhood talent interests so that it is more effective and efficient.